PERANCANGAN MODEL PENENTUAN JUMLAH KARYAWAN YANG OPTIMAL PADA PT INFINEON TECHNOLOGIES BATAM - Siddiq, Azumar; hasibuan, Rizki (LPPM Universitas Putera Batam, 2022)
PT Infineon Technologies Batam is a semiconductor manufacturer specializing in the assembly and testing of chips/integrated circuits. PT Infineon Technologies Batam is experiencing an increase in customer/customer demands of material. therefore management is indefinitely increasing the volume of production. This study aims to design a model to optimize the number of employees in warehouse logistics. Currently, there is no specific measure to optimize the number of employees needed in the areas of the stuffing and issuing operation, the delivery and supply operation and the operation of the PPC store, the problem is that the warehouse logistics department has a staff of only 2 employees in the stuffing and issuing operation, 1 employee in the delivery and supply operations and 1 employee in the store PPC. The purpose of the research is to collect data on job descriptions to calculate the workload and the optimal number of workers through the method of workload analysis. The results of the workforce workload analysis implemented with data on the total needs/requirements in the field of prank and issue operations remain 2 employees, in the field of operations delivery and supply, there are 2 employees and in the PPC Store area, there is another 1 workforce. Realize the design model of the optimal number of employees by combining the number of employees, the demand and the time expenditure with the application of the enterprise device system to obtain the results of the variable demand, the optimal number of employees efficiently.